Exploring motor imagery as a therapeutic intervention for Parkinson’s disease patients: a scoping review - Michel, Maxime; Terragno, Elena; Bereau, Matthieu; Magnin, Eloi; Gueugneau, Nicolas; Soares, Antonio Vinicius; Sagawa, Yoshimasa (Frontiers in Neurology, 2024)
Background Motor imagery (MI) has emerged as a promising therapeutic approach for Parkinson’s disease (PD). MI entails mentally rehearsing motor actions without executing them. This cognitive process has garnered attention due to its potential benefits in aiding motor function recovery in patients. The purpose of this review was to highlight the findings observed in motor symptoms, balance, gait, and quality of life. Methods A literature search was carried out in Medline, Embase, Cochrane, and Physiotherapy Evidence Database (PEDro), from the first publication to February 2024. Studies with at least one keyword to PD and MI in the title were included. Results The analysis included 53 studies out of the 262 identified. These comprised 12 randomized controlled trials (RCTs) with an average PEDro score of 6.6 out of 10, as well as 41 non-RCT studies. Notably, the majority of the RCTs focused on balance, gait, and lower limb exercises. The experimental group found an 85.2% improvement on the Timed Up and Go (TUG) with a cognitive task (p < 0.02), 5.8% improvement on the TUG (p < 0.05), and 5.1% improvement in walking speed (p < 0.05). Other variables did not show significant improvement. In descriptive and non-RCT studies, there were various tasks and outcomes for the lower and upper limbs. It has been demonstrated that there was no difference in execution time in MI between patients and healthy subjects (HS), whereas motor execution was slower in patients. Several tasks were analyzed for the upper limb, including thumb opposition, joystick movements, and writing tasks with variable results. RCTs were more focused on balance, lower limbs, and walking. There was no specific outcome regarding the upper limb or speech. Additionally, the heterogeneity of tasks and outcomes across studies is also a limitation. Conclusion Current research on walking disorders in PD shows promise, but further investigations are crucial, particularly with an emphasis on upper limb function and speech. Studies with larger sample sizes and more precise methodologies are needed to enhance our understanding of the potential benefits of MI within the framework of comprehensive PD rehabilitation.